GE_GERICHTE P/1207/2019 vom 8. Dezember 2025 - GE Cour de justice (2025)
ASSASSINAT;MEURTRE;FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;INTERNEMENT(DROIT PÉNAL);TRAITEMENT AMBULATOIRE;TORT MORAL;EXCÈS;LÉGITIME DÉFENSE | CP.112; CP.111; CP.16; CP.47; CP.49; CP.64; CP.63; CO.49